Pendidikan Anak dalam Keluarga Perspektif Islam - As'ad (Ability: Journal of Education and Social Analysis, 2021)
The children’s education in the family start from their parents, they must respect each other and carry out their obligations. In addition, they are also required to improve themselves to become shaleh and shalehah to fear Allah SWT. This condition is a major milestone in family education. Parents habits in harmony and obedience to Allah can affect their children as learners in the family. Then the children’s education in the family, there are at least five main orientations. The components of education for children are faith orientation, worship orientation, moral orientation, family orientation, and social orientation. The method and type of data collection in this research is library research by collecting books, journals, and previous research results that support the research theme, including literature on children's education in the Islamic perspective of the family. The research process begins with the following stages: identifying and finding information relevant to the theme of quality assurance, then analyzing the findings, and then developing and expressing them into new findings related to children's education in an Islamic perspective family.